2020
DOI: 10.1152/japplphysiol.00562.2020
|View full text |Cite
|
Sign up to set email alerts
|

Molecular markers of skeletal muscle hypertrophy following 10 wk of resistance training in oral contraceptive users and nonusers

Abstract: Objective: to determine whether skeletal muscle molecular markers and SC number were influenced differently in users and non-users of oral contraceptives (OCs) following 10 weeks of resistance training Methods: Thirty-eight young healthy untrained users (n=20) and non-users of OC (n=18) completed a 10-week supervised progressive resistance training program. Before and after the intervention a muscle tissue sample was obtained from the vastus lateralis muscle for analysis of muscle fiber cross sectional area (f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 52 publications
(52 reference statements)
1
16
0
Order By: Relevance
“…The western blotting protocol followed standard procedures described in more detail in Oxfeldt et al [ 38 ]. In short, protein samples were separated using a sodium dodecyl sulfate (SDS)-polyacrylamide gel and electroblotted onto polyvinylindene difluoride (PVDF) membranes before being blocked and incubated in primary antibodies overnight.…”
Section: Methodsmentioning
confidence: 99%
“…The western blotting protocol followed standard procedures described in more detail in Oxfeldt et al [ 38 ]. In short, protein samples were separated using a sodium dodecyl sulfate (SDS)-polyacrylamide gel and electroblotted onto polyvinylindene difluoride (PVDF) membranes before being blocked and incubated in primary antibodies overnight.…”
Section: Methodsmentioning
confidence: 99%
“…Of 5438 potential records identified from database searches, 50 were included (figure 1)34–83 incorporating data from 5 695 908 participants from 48 unique cohorts 34 35 38–66 69–83…”
Section: Resultsmentioning
confidence: 99%
“…Included studies are summarised in online supplemental file 1. Three were RCTs (6%),35 43 74 14 were quasi-experimental (28%),46 47 49 50 52 56 62 64–66 76 77 79 83 25 were prospective cohort studies (50%)38–42 44 45 48 51 53–55 57 60 61 63 69–72 75 78 80–82 and 8 were retrospective cohort studies (16%) 34 36 37 58 59 67 68 73…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Wikstrom-Frisen et al found no significant differences in strength, squat jump ability, or isokinetic peak torque between women who used OCs and those who did not [ 52 ], while Nichols et al found no differences in isokinetic torque and maximum strength gain between female student athletes who used OCs and those who did not [ 22 ]. According to Oxfeldt et al, 10 weeks of resistance training increased ‘muscle regulatory factor 4’ expression levels as well as satellite cell numbers in women who used OCs compared to nonusers [ 53 ], and Dalgaard et al reported that the use of third-generation OCs was associated with an increase in muscle mass [ 54 ]. These data indicate that OC use does not negatively influence strength and appears not to interrupt the anabolic response of muscles to resistance exercise [ 15 , 19 , 55 ].…”
Section: Discussionmentioning
confidence: 99%